"Courage to take on the bull": Cultural citizenship in fifth-grade social studies. (2nd January 2021) - Falkner, Anna; Payne, Katherina A.
ABSTRACT: Critiques of traditional civic education as exclusionary toward individuals and groups that are linguistically, culturally, and age-diverse have led to critical civic education that foregrounds the experiences and assets of Communities of Color. Elementary-aged Children of Color face civic marginalization because of their multiple identities, including culture and age. We present a case study of one white fifth-grade teacher, Ms. Vine, and her two classes of culturally and linguistically diverse students who engaged in critical social studies content that created opportunities for students to use and learn about cultural citizenship. We highlight three cultural citizenship practices seen across students' engagement with social studies content. First, students engaged in self-definition and identity work, laying the groundwork for further critical civic education. Second, the class interrogated issues of injustice and civic action through attention to counternarratives inclusive of Children and Communities of Color as civic actors. Finally, students grappled with historical agency in counternarratives and negotiated agency within the classroom. These cultural citizenship practices enabled Black and Brown children to draw on their civic assets, engage a conception of civicness reflective of people like themselves, and forwarded critical elementary social studies practices.